2014
DOI: 10.18472/sustdeb.v5n2.2014.11428
|View full text |Cite
|
Sign up to set email alerts
|

“Não existirá agroecologia sem feminismo”:

Abstract: Cet article propose de montrer comment le genre fait partie intégrante de la réflexion de base sur la construction de l’agroécologie comme nouveau paradigme. Si tous les défenseurs de l’agroécologie n’intègre pas une analyse genrée, ni la lutte contre les inégalités, de nombreux mouvements sociaux, notamment les mouvements de femmes rurales, critiquent cet « aveuglement au genre » et en dénoncent les conséquences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Durante a inauguração do EAV, o movimento feminista alçou uma presença significativa, representado por mulheres engajadas e discursos que enfatizaram o protagonismo feminino na agricultura (codificação "movimento feminista" nas Tabelas de 2 a 5). Estudos apontam para a relação entre agroecologia e movimento feminista, destacando a participação das mulheres na produção de negócios agroecológicos e na agricultura familiar MATTOS, 2017;PRÉVOST et al, 2014).…”
Section: Análise Dos Resultadosunclassified
“…Durante a inauguração do EAV, o movimento feminista alçou uma presença significativa, representado por mulheres engajadas e discursos que enfatizaram o protagonismo feminino na agricultura (codificação "movimento feminista" nas Tabelas de 2 a 5). Estudos apontam para a relação entre agroecologia e movimento feminista, destacando a participação das mulheres na produção de negócios agroecológicos e na agricultura familiar MATTOS, 2017;PRÉVOST et al, 2014).…”
Section: Análise Dos Resultadosunclassified
“…Thus, the family farmer unions argue that while it is critical to continue awareness-raising work to reduce pesticide use, having a positive agenda is more mobilising with decision-makers who, for the most part, consider soy to bring development. The unions wish to evidence that the consolidation of family farming is also fundamental for the future of the region, whether to ensure food sovereignty, preserve the environment, empower women, or guarantee decent work in rural communities, as many authors have shown (ALTIERI; TOLEDO, 2011; PRÉVOST; ESMERALDO; GUETAT-BERNARD, 2014). This opens important avenues of collaboration for us within the Odisseia observatory to better understand ongoing agroecological experiments (PIVA et al, 2022) and what conditions would allow farming communities to consolidate from these initiatives.…”
Section: Discussionmentioning
confidence: 99%